Wasteland Modernism: The Disenchantment of Myth (2021)
This book proposes a renewed myth-critical approach to the so-called ‘wasteland modernism’ of the 1920s to reassess certain key texts of the American modernist canon from a critical prism that offers new perspectives of analysis and interpretation. Myth-criticism and, more specifically, the critical survey of myth as an aesthetic and ideological strategy fundamental for the comprehension of modernist literature, leads to an engaging discussion about the disenchantment of myth in modernist literary texts. This process of mythical disenchantment, inextricable from the cultural and historical circumstances that define the modernist zeitgeist, offers a possibility for revising from a contemporary standpoint a set of classic texts that are crucial to our understanding of the modern literary tradition in the United States. This study carries out an exhaustive and updated myth-critical examination of works by T.S. Eliot, John Dos Passos, F. Scott Fitzgerald, Ernest Hemingway, John Steinbeck and Djuna Barnes to broaden the scope of familiar themes and archetypes, enclosing the textual analysis of these works in a wider exploration about the purpose and functioning of myth in literature, particularly in times of crisis and transformation.Este libro propone una renovada aproximación mítico-crítica al llamado “wasteland modernism” de la década de 1920 para reevaluar ciertos textos clave del canon modernista norteamericano desde un prisma crítico que ofrece nuevas perspectivas de análisis e interpretación. La mitocrítica y, más concretamente, el estudio crítico del mito como estrategia estética e ideológica fundamental para la comprensión de la literatura modernista, conduce a una atractiva discusión sobre el proceso de desencanto del mito en esta, que es inextricable de las circunstancias culturales e históricas que definen el espíritu modernista, y ofrece la posibilidad de revisar desde un punto de vista contemporáneo un conjunto de textos clásicos cruciales para comprender la tradición literaria moderna en Estados Unidos. Este estudio lleva a cabo un exhaustivo y actualizado examen mítico-crítico de obras de T. S. Eliot, John Dos Passos, F. Scott Fitzgerald, Ernest Hemingway, John Steinbeck y Djuna Barnes para ampliar el alcance de los temas y arquetipos conocidos, incluyendo el análisis textual de estas obras en una exploración más extensa sobre el propósito y el funcionamiento del mito en la literatura, particularmente en tiempos de crisis y transformación.
Keywords: Modernism; Wasteland; Myth-criticism